Analisis Blue Ocean Strategy Pada Perusahaan Wings Group - Any Setyarini (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2021)
The dynamics of corporate business competition today is very dynamic, it can be seen from the variety of products issued by the company. This article discusses the role of the blue ocean strategy in the wings group company. The method used is a literature review from several journal sources and related articles. The results of this article confirm that the existence of a blue ocean strategy in which a renewable innovation can improve the company's performance for the better in the eyes of consumers. Other results revealed in this article if a company wants to win the market competition should pay attention to market segmentation, and current market trends. In addition, it must pay attention to the needs and desires of consumers about products that are liked and not liked, this will make the company more aware of the company's position in the market.